2020
DOI: 10.1177/1470785320921011
|View full text |Cite
|
Sign up to set email alerts
|

The role of shopping mission in retail customer segmentation

Abstract: In retailing, it is important to understand customer behavior and determine customer value. A useful tool to achieve such goals is the cluster analysis of transaction data. Typically, a customer segmentation is based on the recency, frequency, and monetary value of shopping or the structure of purchased products. We take a different approach and base our segmentation on the shopping mission—reason why a customer visits the shop. Shopping missions include focused purchases of specific product categories and gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The electricity load curve of electricity customers is clustered by Pan using R -based parallelized K Means algorithm [17]. Sokol proposed a model for segmenting customers alongside the traditional methods [18]. Chan proposed a novel approach for the clustering of consumption behavior [19].…”
Section: Discussionmentioning
confidence: 99%
“…The electricity load curve of electricity customers is clustered by Pan using R -based parallelized K Means algorithm [17]. Sokol proposed a model for segmenting customers alongside the traditional methods [18]. Chan proposed a novel approach for the clustering of consumption behavior [19].…”
Section: Discussionmentioning
confidence: 99%
“…To better leverage customer-segmentation marketing strategies, many scholars have analyzed and studied relevant sales data. Scholars such as Sokol and Holý (2021) have utilized data clustering analysis techniques to analyze customer behavior and value in the retail industry. This study obtained information on shopping proximity, frequency, and purchasing power by segmenting customers and applied data-clustering analysis to a chain pharmacy.…”
Section: Related Workmentioning
confidence: 99%
“…The statement focused on the limitation of mass marketing in a period where data-driven technological possibilities arose to analyze web-users footprints and enable personalized-oriented marketing. About two decades later personalized-oriented marketing is still a key challenge that many researchers conduct in their work (Chen et al 2018;Apichottanakul et al 2021;de Marco et al 2021;Nguyen 2021;Sokol and Holy 2021). Not only has it been shown that personalized customer targeting is more profitable for companies, but also that knowledge about customer behavior is a decisive factor for success and failure (Mulhern 1999;Zeithaml et al 2001;Kumar et al 2008).…”
Section: Introductionmentioning
confidence: 99%